Określanie wartości surowca drzewnego drzewostanów w procesie optymalizacji użytkowania rębnego - Zaborski, Karol; Banaś, Jan; Kożuch, Anna (Leśne Prace Badawcze, 2020)
Forest managers conducting sustainable forest management are guided by the principles of sustainable use of natural resources, which involve the need for long and short-term planning in organizational units of the State Forests. Plans often differ from reality by the time individual treatments and cuts are to be performed. For economic reasons, it is important to optimize harvest planning, not only focusing on the volume of timber to be harvested, but also the price differences of individual tree species and sort types of wood. The purpose of this study was to present methods evaluating standing timber and to assess their usefulness in optimizing the harvest volume using linear programming. Stands designated to be cut were evaluated using transaction value methods, i.e. „the stumpage value method” M1, the „consumption value” method M2, as well as the net present value (NPV) method M3. The research material was obtained from the State Forests Information System (SILP) for the Marcule Forest District covering the years 2014-2018. The stand values were determined at the beginning and end of the 10-year planning period. We observed that the stand value (standing timber) differed significantly between method M2 as compared to method M1. The value of stands determined by method M3, on the other hand, decreased as the discount rate increased. In the process of optimizing the selection of stands for felling, economic criteria should also be taken into account and this is a direct measure of obtainable standing timber in terms of the cutting possibility in the given planning period. In stands where one species dominates, a simplified method of determining the value (M1) can be used, whereas in stands with significant species diversity, method M2 provides a significantly more accurate value for the cutting timber. However, if harvest volume optimization using linear programming methods is to take longer time periods into account, e.g. 30 years (three 10-year economic planning periods), the most reasonable method for determining the value of stands is the net present value method M3.